Analyzing the Use of Formal Links through Classroom Interaction at Islamic Boarding School - Musfirah, Musfirah; Weda, Sukardi; Halim, Abdul (Har Press Indonesia, 2023)
This study deals with the kinds of formal links used in classroom interaction at the Islamic Boarding School by an English teacher and female students in class XI. It aims to describe the kinds of formal links used in classroom interaction, to find out the most frequent kinds of formal links used in classroom interaction, and to find out the extent the students use formal links effectively in classroom interaction at the Islamic Boarding School. This research was carried out by using descriptive qualitative. The researcher used an observation checklist, interview, and audio recording. The data of transcription were classified into seven kinds of formal links. They were verb forms, parallelism, referring expression, repetition, substitution, ellipsis, and conjunction. The researcher observed the English teacher and twenty-two female students in class XI at the Islamic Boarding School. From the English teacher and twenty-two female students in class XI at the Islamic Boarding School who had been observed, the researcher discovered numbers of utterances and percentages. Their total utterances were classified into seven kinds of formal links. The most frequent kind used in classroom interaction was verb forms. Most of the students effectively used formal links in their classroom interaction. On the other hand, some students faced difficulties in using formal links correctly and effectively in classroom interactions.